Exploring the potential of dermal fibroblast conditioned medium on skin wound healing and anti-ageing - Shiplu Roy Chowdhury,; Lim, Shaun Jing; Muhammad Noor Haziq Zolkafli,; Nur’ Aqilah Mohd Abu Zarin,; Wan Alyani Wan Abdullah,; Nurul Aidah Md Mothar,; Manira Maarof,; Nur Atiqah Haizum Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Skin ageing is associated with a decrease in collagen and delayed wound healing. The previous study has shown that supplementation of growth factors can enhance the production of extracellular matrix (ECM) and efficiency of wound healing. This study aimed to produce a Dermal Fibroblast Conditioned Medium (DFCM) and evaluate its potential on in vitro skin wound healing and anti-ageing properties. DFCM were obtained by culturing confluent human dermal fibroblasts (n=3) in keratinocyte-specific medium (DFCM-KM), fibroblast-specific medium (DFCM-FM) and fibroblast-specific medium with growth supplements (DFCM-GM). Protein concentration was determined by Bicinchoninic Acid (BCA) assay. To evaluate the wound healing and anti-ageing properties, human dermal fibroblasts were supplemented with three different DFCM. Fibroblasts cultured with F12:DMEM+10%FBS was used as a control. The growth rate of fibroblasts was evaluated by culturing cells until day 4. Migration rate was evaluated at 12 h after seeding. In vitro healing rate was evaluated via scratch assay. Anti-ageing potential of DFCM was evaluated via RT2 Profiler PCR Array. Concentration of total protein was found to be significantly higher in DFCM-GM (2914.79±150.67mg/mL) compared to DFCM-KM and DFCM-FM. Out of the tested 12 anti-ageing genes, fibroblasts supplemented with DFCM-GM demonstrated a significantly higher expression of WRN compared to other conditions. In conclusion, DFCM-GM contains more proteins and found superior in modulating wound healing and anti-ageing properties.